Role of Service Marketing Mix in Developing Tourism Promotion Tactics and Marketing Strategies - AHAMMED K, Dr. MUSHTHAQ (IJRDO - Journal of Business Management, 2017)
Tourism Promotion and marketing strategies serve as the fundamental groundwork of marketing plans designed to fill market needs and reach tourism marketing objectives which have measurable results. It is possible to write a tactical marketing and promotional plan without a sound and well-considered marketing strategy, but without a sound marketing strategy a marketing plan has no foundation. A marketing strategy often integrates an organization's marketing goals, policies, and action sequences (tactics) into a cohesive whole. Marketing strategies are dynamic and interactive. They are partially planned and partially unplanned. The particular combination of the tourism marketing mix used by any organisation needs to offer it a competitive edge or differential advantage in the target market segment. This means that the marketer is creating something unique that the potential customer will recognise and value, and something that is distinguishable from competition. The edge or advantage may be created mainly through one element of the mix, or through a combination of them